Some Ideas on the References of Legendary Typology of The Holy Fāṭima - Güldane Gündüzöz (Dini Araştırmalar)

(untitled)
HistoricallyFāṭima the daughter of Muḥammad b. ʿAbd Allāh, the Prophet of Islam, by hisfirst wife, Khadīja b. Khuwaylid has an ontological and eschatological meaningin Shīʿī thought. It is important to reveal the nature of this situation and toanalyze the analogy with the Sacred Mary. Figure of Fāṭima is very different inthe Shīʿī thought system. There is a system ofthinking that transcends historical data. An image of the Sacred Fāṭima, whichhas an active role in both existential and eternal dimension is envisaged inthis thought. This conception played a role in the institutionalization oftheImāmī Shīʿī theory within the Shīʿī tradition. Fāṭima’s charisma wasorganized in a similar way to the Saint Mary’s. This charisma has aspects ofthe hereafter such as intercession and mediation. This charisma also hasworldly indicators of healing. Sacred Fāṭima and Mary is evaluated in a similar“ordeal” event. This analogy shows itself in various nomenclature, virginity,fertility, chastity, intercession, healing and fertility, becoming a celestialbeing, coming to the world as a divine being subjects. Finally on one hand Fāṭimafigure is shaped as a spiritual source in a ahistorik structure, on the otherhand, as in the notion of Virgin Mary, it took an iconographic form in theShīʿī thought. Thus Fāṭima is conceived as an intercessor of wisdom, close tothe mediatrix concept in Christianity in the Shīʿī thought system. Sacred Fāṭimawas accepted as a source of healing and fertility. Especially this figure isimpressed by Sacred Mary as much as she is influenced by “The Umayiyesi-UmayAna Figure” in the Altaic area. As a result of this icon appeared in the formof “Hamsa: Hand of Fāṭima” in Shīʿī public. This paper examines how theimportant and respected Fāṭima is judged to be a reference point for certainbeliefs and acceptances in perspective of historical and religious. Similarlythis paper examines how Fāṭima has been transformed into a cult entity in Shīʿīthought. As a result of this transformation, Fāṭima’s image is used as areference in the Shīʿī literature in formation of upper concepts such as ImāmīShīʿism, custody and intercession. This article examines the conversion ofhistorical and religiously important and respected Sacred Fāṭima into a cultentity.